Wound healing in diabetic: a review of photobiomodulation therapy applications (Research, Society and Development, 2020)
Objective: In order to identify the available scientific production regarding photobiomodulation therapy in wound repair associated with diabetes mellitus. Methodology: This is an integrative review seeking primary studies conducted in the databases MEDLINE, LILACS, and SCOPUS, from 2015 to 2020. Results: It was analyzed 18 articles. The year that most published articles related to the theme was 2016 and 2018 with 28 % of articles each. Regarding the place of study 72 % of them were international and 28 % national. Regarding the analysis of the evidence levels of the articles, 94 % of the articles were in level 2 of evidence. As for the samples used in the studies, 50% of the studies used in vivo samples, 39 % clinical samples and 11 % ​​were in vitro. 83 % used laser, 11 % ​​used LED and 6 % used two (laser and LED). At about the power density used, it ranged from 1.08 mW / cm2 to 1920 mW/cm2. Energy density ranged from 0.2 J/cm2 to 6 J/cm2. The power ranged from 5 mW to 80000 mW. Application time ranged from 12 to 1066 seconds. The most commonly used wavelength was 660 nm. Conclusion: Studies rectify the efficacy of photobiomodulation therapy alone or in combination with other treatments, humans as well as animals or in vitro, in wound repair associated with diabetes mellitus.